Pollen and Isotope Investigations of an Ice Core from Vavilov Ice Cap, October Revolution Island, Severnaya Zemlya Archipelago, Russia - Andreev, Andrei; Nikolaev, Vladimir; Boi’sheiyanov, Dmitrii; Petrov, Vladimir (Géographie physique et Quaternaire, 1997)
SUMMARYThe Vavilov Ice Cap (79°27'N, 95° 21'E) was cored during February and March of 1988. The corer passed through 457.18 m of glacier ice, 2.15 m of moraine-containing ice, and 2.28 m of underlying rocks. Structural-stratigraphical and isotope analysis show the glacier ice is of Holocene in age; the ice layer covered by frozen deposits is Pleistocene glacier ice; and the ground (ice wedge?) ice from underlying sediments was formed during the Last Interglacial. Palynological studies of this core, carried out for the first time in the Russian Arctic demonstrate that the pollen spectra have a unique pattern. It reduces the possibility of correlation between the Vavilov Ice Cape spectra and pollen spectra from other surficial deposits, because the ice retains pollen and spores brought from enormous distances. Only the upper 65 m of the core is easily dated, to the last millennium, by the presence of cereals, Plantago lanceolata, Centaurea cyanus, Cannabis pollen. That is in good agreement with the model of age distribution based upon depth. The presence of considerable amounts of Tilia cordifolia pollen, a West-European species in the upper layers suggests that summer air masses have been dominantly from the southwest during the last 500 years. The pollen data do not contradict the conclusion the Vavilov ice core is composed of a section of Holocene ice, moraine-containing ice representing the Pleistocene episode, and a ground ice formed during an earlier warm period (Last Interglacial?).